Role of CYP2A5 in the Bioactivation of the Lung Carcinogen 4-(Methylnitrosamino)-1-(3-Pyridyl)-1-Butanone in Mice - Zhou, Xin (The American Society for Pharmacology and Experimental Therapeutics, 2012)
The tobacco-specific nitrosamine 4-(methylnitrosamino)-1-(3-pyridyl)-1-butanone (NNK) is a potent lung carcinogen. Previously, we have demonstrated that NNK-induced lung tumorigenesis in mice depends on target-tissue bioactivation by pulmonary cytochrome P450 (P450) enzymes. The present study was designed to test the hypothesis that mouse CYP2A5 plays an essential role in NNK bioactivation in mouse lung. The role of CYP2A5 in NNK bioactivation was studied both in vitro and in vivo, by comparing the kinetic parameters of microsomal NNK metabolism and tissue levels of O(6)-methylguanine (O(6)-mG) (the DNA adduct highly correlated with lung tumorigenesis) between wild-type (WT) and Cyp2a5-null mice. In both liver and lung microsomes, the loss of CYP2A5 resulted in significant increases in the apparent K(m) values for the formation of 4-oxo-4-(3-pyridyl)butanone, which represents the reactive intermediate that produces O(6)-mG in vivo. The loss of CYP2A5 did not change circulating levels of NNK or 4-(methylnitrosamino)-1-(3-pyridyl)-1-butanol in mice treated intraperitoneally with NNK at either 20 or 100 mg/kg. However, the levels of lung O(6)-mG were significantly lower in Cyp2a5-null than in WT mice; the extent of the reduction was greater at the 20 mg/kg dose (∼40%) than at the 100 mg/kg dose (∼20%). These results indicate that CYP2A5 is the low-K(m) enzyme for NNK bioactivation in mouse lung. It is noteworthy that the remaining NNK bioactivation activities in the Cyp2a5-null mice could be inhibited by 8-methoxypsoralen, a P450 inhibitor used previously to demonstrate the role of CYP2A5 in NNK-induced lung tumorigenesis. Thus, P450 enzymes other than CYP2A5 probably also contribute to NNK-induced lung tumorigenesis in mice.